ALCHEMISTS, WIZARDS, ADEPTS: ESOTERIC PATTERNS OF THOUGHT AND INTERPRETATION IN REPORTING ON FINANCE (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
This paper analyzes metaphors in the field of esoterics used in articles in the German media dealing with the financial sector. The aim of the research is to answer the question, what do these metaphors tell us about the understanding of the financial economy and its actors. Starting from the thesis that interpretive schemes are sedimented in metaphors, the question arises as to which lay theories ("folk theories") on the functioning of the financial economy can be reconstructed from newspaper articles. The analysis was done using cognitive semantics methods on a corpus of 156 articles published in three leading German media in the midst of the 2008/2009 financial crisis. Based on empirical analysis, it is concluded that the financial economy in the German public is generally perceived as a parallel world, which operates according to some strange and mysterious laws. By analyzing metaphors, two central interpretive schemes are reconstructed: bankers are perceived as wizards, magicians and alchemists, who make money with ease and without hard work; and bankers are characterized as sorcerers and fraudsters who get rich with various tricks and deception to the detriment of their clients.
Keywords: financial sector; banks; metaphors; esoretics; interpretive schemes